Essai bibliographique sur l'archéologie francophone de la mésoamérique = Bibliographical essay upon the French-speaking contributions to Mesoamerican archaeology = Ensayo bibliográfico sobre la arqueología francófona de mesoamérica - Taladoire, Eric, (Access archaeology., 2019)
The present bibliography of contributions in French to Mesoamerican studies aims to serve several purposes. For more than a century, Spanish, English and French were the three official languages of the International Congresses of Americanists. This situation stems from historical reasons: the first Congresses took place in Nancy, Luxemburg and Brussels. Since the fifties, the steady growth of Mexican and Central American national researches and the ever-growing weight of United States investigators slowly occulted the French contributions. Conversely, the establishment of research institutions in Belgium, Switzerland, France and Canada facilitated the multiplication of investigation projects in the whole continent, with their correlative publications.